THE EFFECT OF TRIPLE-GLAZED WATER FLOW WINDOWS ON COOLING ENERGY CONSUMPTION - Koca, Ahmet; Yamaç, Halil İbrahim; Gür, Muhammed (My University, 2026)
A novel idea called the Water Flow Window (WFW) involves a regulated water flow in the space between two glazing panes. Running water in the summer can greatly lessen the heat gain in the room. This study is carried out in summer for triple-glazed windows in Elazig. The electrical energy savings rate of the cooling systems obtained with the WFW system design compared to normal windows. One side of the cabinets used in the experimental study is completely windowed, while the other facades are made with insulation material on the upper and lower parts. The experimental cabinets’ dimensions are 30x35x75 cm. As the water flow rate rises, the consumption rates fall. At the end of the experimental days, the minimum consumption (daily total) ratio of cooling devices of testing cabinets is around 0.33 and the maximum ratio of cooling devices is around 0.44 at the lowest flow rate.
Keywords: Enerji ve Yakıtlar; İnşaat ve Yapı Teknolojisi